Lipid Production from Arundo Donax Grown under Different Agronomical Conditions - Pirozzi, Domenico; Fiorentino, Nunzio; Impagliazzo, Adriana; Sannino, Filomena; Yousuf, Abu; Zuccaro, Gaetano; Fagnano, Massimo (Elsevier, 2015)
Hydrolysates of Giant reed (Arundo donax) biomass from three different agronomical conditions were used to grow the oleaginous yeast L. Starkey. The agronomical conditions affected the cellulose fraction of biomass, the amount of inhibitors generated during the acid hydrolysis, and the triglyceride yield after the yeast fermentation. Yet, the composition of triglycerides was not affected. Different approaches were developed to reduce the effect of inhibitors. The preliminary dilution of hydrolysates was studied, obtaining the highest values of biomass and lipid yields with a 50% dilution. Alternatively, the hydrolysates were pre-treated by adsorption and overliming. The latter pre-treatment gave the best results. A third approach was offered by the use of pre-adapted yeasts, that were able to grow in the presence of raw hydrolysates. The composition of the microbial triglycerides was compatible with the production of a biodiesel suitable for use as automotive fuel.